2021
DOI: 10.1002/aet2.10580
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of lesbian, gay, bisexual, and transgender health education and training in emergency medicine residency programs: Where are we now?

Abstract: Background: Despite identified inequities and disparities in lesbian, gay, bisexual, transgender, queer, and questioning (LGBTQ+) health, past studies have shown little or no education at the medical school or residency level for emergency physicians. With increased focus on health inequities and disparities, we sought to reexamine the status of sexual and gender minority health education in U.S. emergency medicine (EM) residencies. Objectives: Our primary objective was to determine how many EM residencies off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…And while we found that involvement of transgender perspectives in developing and delivering content was beneficial for student learning and part of necessary advocacy work, some authors warn of overburdening people with lived experiences (including transgender students), in particular when experiential knowledge cannot be properly compensated (Bi et al, 2020 ; Biro et al, 2021 ). Finally, there is concern about how to optimize learner gain; currently, no conclusive evidence exists as to which timing, modality, and method of implementation effectively contributes to student learning and clinical outcomes (Altneu et al, 2020 ), while the everyday conditions of graduate, undergraduate and residency programs hinder initial implementation of curricula (Donovan et al, 2021 ; Moll et al, 2021 ). All of this suggests that currently, medical curricula are lagging to take a key role as intervention sites for reducing and eliminating transgender health inequities (Giffort & Underman, 2016 ; Pregnall et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…And while we found that involvement of transgender perspectives in developing and delivering content was beneficial for student learning and part of necessary advocacy work, some authors warn of overburdening people with lived experiences (including transgender students), in particular when experiential knowledge cannot be properly compensated (Bi et al, 2020 ; Biro et al, 2021 ). Finally, there is concern about how to optimize learner gain; currently, no conclusive evidence exists as to which timing, modality, and method of implementation effectively contributes to student learning and clinical outcomes (Altneu et al, 2020 ), while the everyday conditions of graduate, undergraduate and residency programs hinder initial implementation of curricula (Donovan et al, 2021 ; Moll et al, 2021 ). All of this suggests that currently, medical curricula are lagging to take a key role as intervention sites for reducing and eliminating transgender health inequities (Giffort & Underman, 2016 ; Pregnall et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite recent efforts to increase LGBTQIA+ health care training, these endeavors are insufficient—the pathologizing of being TGE and conflation of gender diversity with mental illness were commonly reported by our participants. 17 , 18 , 19 In line with prior literature, educational interventions should target transphobia rather than simply provide informational and/or clinical knowledge. 20 Training programs and institutions should partner with transgender-led organizations that facilitate this education, and the training should span all career stages.…”
Section: Discussionmentioning
confidence: 72%
“…Formal education on the care of LGBTQIA+ persons is inadequate at both the undergraduate medical education level (median 5 h of curriculum) and EM residency level (median 2 h per academic year). [9][10][11] A survey of EM residents reported that 24.6% found it challenging to do a history and physical on LGB patients, and 42.6% on transgender patients. 12 In that same survey, 6% of residents did not agree that…”
Section: Current State Of Knowledge On the Lgbtqia+ Communitymentioning
confidence: 99%